Evaluation of agonist and antagonist radioligands for somatostatin receptor imaging of breast cancer using positron emission tomography - Iulia Dude; Zhengxing Zhang; Julie Rousseau; Navjit Hundal-Jabal; Nadine Colpo; Helen Merkens; Kuo-Shyan Lin; François Bénard (SpringerOpen, 2017)
Abstract Background The somatostatin receptor subtype 2 (sstr2) is expressed on a majority of luminal breast cancers, however SPECT and scintigraphy imaging with agonistic sstr2 probes has been sub-optimal. High affinity antagonists can access more binding sites on the cell surface, resulting in higher tumor uptake and improved sensitivity. We compared the tumor uptake and biodistribution of the antagonist 68Ga-NODAGA-JR11 with two agonists 68Ga-DOTA-Tyr3-octreotide (68Ga-DOTATOC) and 68Ga-DOTA-Tyr3-octreotate (68Ga-DOTATATE), in the human, sstr2-positive, luminal breast cancer model: ZR-75-1. Results Peptides were assayed for binding affinity using a filtration-based competitive assay to sstr2. natGa-DOTATOC and natGa-DOTATATE had excellent affinity (inhibition constant Ki: 0.9 ± 0.1 nM and 1.4 ± 0.3 nM respectively) compared to natGa-NODAGA-JR11 (25.9 ± 0.2 nM). The number of binding sites on ZR-75-1 cells was determined in vitro by saturation assays. Agonist 67/natGa-DOTATOC bound to 6.64 ± 0.39 × 104 sites/cells, which was 1.5-fold higher than 67/natGa-NODAGA-JR11 and 2.3-fold higher than 67/natGa-DOTATATE. All three 68Ga-labeled peptides were obtained in good decay-corrected radiochemical yield (61-68%) and were purified by high performance liquid chromatography to ensure high specific activity (137 - 281 MBq/nmol at the end of synthesis). NOD scid gamma mice bearing ZR-75-1 tumors were injected intravenously with the labeled peptides and used for PET/CT imaging and biodistribution at 1 h post-injection. We found that 68Ga-DOTATOC had the highest tumor uptake (18.4 ± 2.9%ID/g), followed by 68Ga-DOTATATE (15.2 ± 2.2%ID/g) and 68Ga-NODAGA-JR11 (12.2 ± 0.8%ID/g). Tumor-to-blood and tumor-to-muscle ratios were also higher for the agonists (>40 and >150 respectively), compared to the antagonist (15.6 ± 2.2 and 45.2 ± 11.6 respectively). Conclusions The antagonist 68Ga-NODAGA-JR11 had the lowest tumor uptake and contrast compared to agonists 68Ga-DOTATOC and 68Ga-DOTATATE in ZR-75-1 xenografts. The main contributing factor to this result could be the use of an endogenously expressing cell line, which may differ from previously published transfected models in the number of low-affinity, antagonist-specific binding sites. The relative merit of agonists versus antagonists for sstr2 breast cancer imaging warrants further investigation, first in preclinical models with other sstr2-positive breast cancer xenografts, and ultimately in luminal breast cancer patients.